Strength and Deflection Reliability Estimation of Girder Steel Portal Frames Using the Bayesian Updating Method - Fahmi, F. H.; Al-Zaidee, S. (Engineering, Technology & Applied Science Research, 2022)
Uncertainty is ubiquitous in any engineering system at any stage of product development and throughout a product’s life cycle. As information and sensor technology develops, more and more data about engineering systems are gathered. A strong technique for calibrating models using new information and observations is Bayesian updating. The applied loads, yield strength, plastic section modulus, span, cross-section dimensions, and modulus of elasticity from the international literature have been updated through the local literature and a data survey for the interior girder portal frames to investigate the reliability index and the probability of failure of the system. First Order Reliability Method (FORM) and Monte Carlo (MC) simulations have been used to estimate the reliability and probability of failure of strength and serviceability limit state function. The results reveal that for shear force, the reliability index increased significantly from 9.03 to 16.01. At the same time, the reliability index of the bending moment and deflection increased from 4.34 to 5.30 and from 6.90 to 7.66 respectively.